Varieties of Religious Authority : Changes and Challenges in 20th Century Indonesian Islam - Kaptein, N. J. G.; Dijk, C. van (Cornelis), 1946-; Azra, Azyumardi (Book collections on Project MUSE., 2010)
The twentieth century was a fascinating period of profound political, social and economic changes in Indonesia. These changes contributed to the diversification of the religious landscape and as a result, religious authority was redistributed over an increasing number of actors. Although many Muslims in Indonesia continued to regard the ulama, the traditional religious scholars, as the principle source of religious guidance, religious authority has become more diffused and differentiated over time. The present book consists of contributions which all deal with the multi-facetted and multidimensional.